ABHD15 regulates adipose tissue lipolysis and hepatic lipid accumulation - Jacqueline Stöckli; Armella Zadoorian; Kristen C. Cooke; Vinita Deshpande; Belinda Yau; Gaia Herrmann; Melkam A. Kebede; Sean J. Humphrey; David E. James (Molecular Metabolism, 2019)
Objective: Insulin suppresses adipose tissue lipolysis after a meal, playing a key role in metabolic homeostasis. This is mediated via the kinase Akt and its substrate phosphodiesterase 3B (PDE3B). Once phosphorylated and activated, PDE3B hydrolyses cAMP leading to the inactivation of cAMP-dependent protein kinase (PKA) and suppression of lipolysis. However, several gaps have emerged in this model. Here we investigated the role of the PDE3B-interacting protein, α/β-hydrolase ABHD15 in this process. Methods: Lipolysis, glucose uptake, and signaling were assessed in ABHD15 knock down and knock out adipocytes and fat explants in response to insulin and/or β-adrenergic receptor agonist. Glucose and fatty acid metabolism were determined in wild type and ABHD15−/− littermate mice. Results: Deletion of ABHD15 in adipocytes resulted in a significant defect in insulin-mediated suppression of lipolysis with no effect on insulin-mediated glucose uptake. ABHD15 played a role in suppressing PKA signaling as phosphorylation of the PKA substrate Perilipin-1 remained elevated in response to insulin upon ABHD15 deletion. ABHD15−/− mice had normal glucose metabolism but defective fatty acid metabolism: plasma fatty acids were elevated upon fasting and in response to insulin, and this was accompanied by elevated liver triglycerides upon β-adrenergic receptor activation. This is likely due to hyperactive lipolysis as evident by the larger triglyceride depletion in brown adipose tissue in these mice. Finally, ABHD15 protein levels were reduced in adipocytes from mice fed a Western diet, further implicating this protein in metabolic homeostasis. Conclusions: Collectively, ABHD15 regulates adipocyte lipolysis and liver lipid accumulation, providing novel therapeutic opportunities for modulating lipid homeostasis in disease. Keywords: Lipolysis, Adipocytes, Insulin action, Fatty acid metabolism, β-adrenergic receptor agonist